NUTRITIONAL SUPPLEMENTS AND THEIR USE IN THE TREATMENT OF MALNUTRITION IN DEVELOPING COUNTRIES - Fatima, Sadia; Khan, Shahbaz Ali; Fatima, Fozia (Journal of Ayub Medical College Abbottabad, 2015)
Background: Despite the high global prevalence of malnutrition, it remains under-treated, or undetected. The high energy nutritional supplements are usually prescribed to promote rapid weight gain. However, there is no consensus on the most effective way to treat mild to moderate malnutrition. Methods: For identification of articles search engines of the databases OVID, MEDLINE, EMBASE and Pub med were used for papers published from 2003 to 2014 in English language. Results: The total energy intake including the supplements is significantly improved. However, the rate of weight gain by the high energy nutritional supplements in moderately malnourished children is less than the expected weight gain. Conclusion: While assessing the impact of the supplementation on child nutritional status, other factors should also be taken into account, including appetite suppression, replacement of habitual food intake and compliance to the intervention.